Filogenia e taxonomia de Rhoadsiinae (Actinopterygii: Characiformes: Characidade) - Lugo, Rafael Acosta (2018)
Rhoadsiinae is one of the 15 subfamilies that compose the family Characidae, proposed in 1911 by Fowler. Its distribution is exclusively trans-Andean and is found in Ecuador, Panama, Colombia, Peru, Costa Rica, and Nicaragua. A combined matrix of morphological and molecular data was analyzed in a scheme of total evidence. Fiftyfour morphological characters were collected, 36 of which were obtained from the literature and 18 were new, for 15 terminal taxa. Amplifications were performed for the genes 16S, COI, Cytb, Myh6 and RAG2, which were also analyzed separately, using probabilistic Bayesian analysis, performed on the CIPRES website. The parsimony analysis was performed in the TNT software, through an exact search (Implicit enumeration) and a heuristic procedure of a thousand Random Addition Sequence (RAS) interactions followed by Tree Bissection Reconnection (TBR) tree rearrangements. The analyzes recovered a single maximally parsimonious tree with 2604 steps, consistency index 0.60 and retention index 0.45. The results corroborate the monophyly of Rhoadsiinae. The subfamily is composed of seven species divided in four genera, six of which are described in previous works and a new genus and species is described in this paper, provisionally named New Táxon "Panamá". In addition, it is demonstrated that the clade of Rhoadsia is the sister to all other genera of the subfamily; Carlana eigenmanni and New Táxon "Panamá" are sister group to each other. The phylogenetic relationships between the species are represented as follows: ((Rhoadsia altipinna + Rhoadsia minor) + ((Carlana eigenmanni + New Táxon "Panama") + (Parastremma sadina (Parastremma pulchrum + Parastremma album)))).